Ethnic Residential Segregation and Immigrants' Perceptions of Discrimination in West Germany - Verena Dill; Uwe Jirjahn (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
Using survey data from the German Socio-Economic Panel, this study shows that immigrants living in segregated residential areas are more likely to report discrimination because of their ethnic background. This applies to both segregated areas where most neighbors are immigrants from the same country of origin as the surveyed person and segregated areas where most neighbors are immigrants from other countries of origin. The results suggest that housing discrimination rather than self-selection plays an important role in immigrant residential segregation.
Keywords: J15; J61; R23; R30; 330; Segregation; immigrants; housing discrimination; self-selection; Migranten; Segregation; Diskriminierung; Wahrnehmung; Deutschland